Jämställdhetsproblematik i praktiken - En analys av jämställdhetsproblematik i rättstillämpningen vid surrogatarrangemang och assisterad befruktning - Månsson,Mikaela (2024)
Surrogacy means that a woman becomes pregnant with the express intention of not keeping the child after birth but handing it over to a couple or another person. The procedure is used to a greater extent today to enable involuntarily childless people to have children. This essay examines surrogacy, but also assisted fertilization, and how parenthood is defined, since problems often arise with parenthood after surrogacy arrangements abroad. The problems that arise can look different depending on gender and sexual orientation, and the essay thus also examines whether there are any gender equality issues in these situations. In Swedish law, there is a presumption of maternity, which means that the person who gives birth to a child becomes the child's legal mother. Problems arise when couples go abroad to undergo surrogacy arrangements and then go back to Sweden. These problems are visible in the Swedish cases NJA 2006 p. 505 and NJA 2019 p. 504. For men in different-sex relationships and the other woman in same-sex relationships, these problems do not arise because there is legal support for determining parenthood. Problems can also arise after undergoing assisted fertilization in another state, which is seen in the Swedish case HFD 2020 ref. 13. When it comes to surrogacy, the legislator has been clear since the 1980s that it is not ethically justifiable and has been considered to involve trafficking in women and children. In addition, the legislator has not wanted to make it easier for people to undergo surrogacy arrangements abroad in the legislation, but rather has opposed these possibilities. One of the gender equality problems that exists in the application of the law is that men can more easily have their paternity established compared to women. Firstly, there is the presumption of maternity, which means that intended mothers are generally not recognized as the mother of a child conceived through surrogacy arrangements. Secondly, women in same-sex relationships have been disadvantaged because there has been no legal support for recognizing parentage established abroad in Sweden. This results in legislative changes probably being required in Sweden.
Keywords: Civilrätt; familjerätt; surrogatmoderskap; surrogatarrangemang; jämställdhet